Pengaruh Customer Perceived Value Dan Customer Experience Terhadap Revisit Intention Pada Objek Wisata - An Nisa Lathifah Nabila; Armida Armida (Universitas Negeri Padang, 2020)
This reseacrh aims to reveal the effect of customer perceived value and customer experience on revisit intention in The Great Wall of Koto Gadang attraction. This research is a causative study. The population in this study were all tourists who had visited the attraction of The Great Wall of Koto Gadang. The data used are primary data and secondary data. Data collection techniques are using questionnaires and documentation. The sample technique used in this study is purposive sampling with a total sample of 100 respondents. The analytical method used is path analysis using SPSS version 21. The research hypothesis testing was carried out using data analysis through validity and reliability, normality, heterokedactivity, path analysis, F test and statistical t test at α = 0.05. The results of this study indicate that 1) customer perceived value and customer experience significantly influence revisit intention 2) customer perceived value significantly influence customer experience 3) customer perceived value significantly influence revisit intention 4) customer experience significantly influence revisit intention. Keywords : customer perceived value, customer experience and revisit intention